2015
DOI: 10.1007/s13594-015-0220-y
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of structures and functions of caseins: a scientific and technological challenge

Abstract: Casein molecules are used in food industry as ingredients. They can be used as isolated forms and under micellar form consisting in an association of different casein molecules and calcium phosphate. In this review, after a brief reminder of the main characteristics of casein molecules and casein micelles, the modifications of caseins induced by physical, chemical, and enzymatic actions are reported. The resulting new physicochemical properties (mineral and casein compositions, charge, hydrophobicity, aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
139
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(148 citation statements)
references
References 217 publications
3
139
0
6
Order By: Relevance
“…For instance, Tang et al [89] studied the susceptibility of non-micellar sodium caseinate to TGase, but the determined order of κ-casein > α S -casein > β-casein might rather be a result of false band assignments. In spite of studies that have shown an order of β-casein > α S -casein > κ-casein, e.g., [77,78,80], this information is still cited in the literature, e.g., [27,102]. On the other hand, it is generally acknowledged that κ-casein is most susceptible to TGase in case of micellar casein because of high accessibility on the micelle surface, e.g., [78,92,[103][104][105][106][107][108].…”
Section: Literature Review Of Studies On Cross-linked Caseinmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Tang et al [89] studied the susceptibility of non-micellar sodium caseinate to TGase, but the determined order of κ-casein > α S -casein > β-casein might rather be a result of false band assignments. In spite of studies that have shown an order of β-casein > α S -casein > κ-casein, e.g., [77,78,80], this information is still cited in the literature, e.g., [27,102]. On the other hand, it is generally acknowledged that κ-casein is most susceptible to TGase in case of micellar casein because of high accessibility on the micelle surface, e.g., [78,92,[103][104][105][106][107][108].…”
Section: Literature Review Of Studies On Cross-linked Caseinmentioning
confidence: 99%
“…This may be achieved through acid precipitation of casein at pH 4.6 [53], which does not affect native whey proteins. After heat treatment, however, β-lactoglobulin is covalently attached to κ-casein via disulphide bonds and will therefore precipitate together with casein [102].…”
Section: Literature Review Of Studies On Cross-linked Caseinmentioning
confidence: 99%
“…Such modifications induce the increase of hydrophilicity, ability to dissociation, evenness of distribution of the surface charge and, correspondingly, correction of functional-technological properties [8,9].…”
Section: Food Science and Technologymentioning
confidence: 99%
“…Yn-CN = (mtotal CN * Pn-CN) / (mMCN * ctotal protein, MCN) * 100 (2) where mtotal,CN refers to the mass of the obtained n-casein fraction, mMCN to the initial mass of micellar casein (MCN) powder used for the isolation, while ctotal protein, MCN refers to the calculated protein content of the micellar casein using the measured the nitrogen content. The recovery (Rn-CN) of each casein fraction is calculated according to Rn-CN = (Yn-CN, fraction / cn-CN, MCN) * 100…”
Section: Calculationsmentioning
confidence: 99%
“…Caseins are widely used in food and non-food applications. They have various important technofunctional properties such as solubility, emulsification, foam formation and stabilization, waterbinding, gelation, heat and acid stability [2][3][4]. They also play an important role in non-food applications such as the production of plastic materials [5], textile fibers [6] and glues [7].…”
Section: Introductionmentioning
confidence: 99%